The distribution of aquilaria spp. in UiTM Jengka forest reserve / Mohammad Khaidir Azman and Mohd Azim Zainal Abidin - Azman, Mohammad Khaidir; Zainal Abidin, Mohd Azim (2008)
The UiTMJFR is a logged-over forest and this area is about 250 acres. This study was recorded the distribution of Aquilaria spp. in UiTMJFR, Line 3 – Line 6 and Line 13 – Line 16. There are from Line 3 to Line 6 and from Line 13 to Line 16 that assume about 4120 meter total sum of all of the Lines length. Survey done by range 5 meter left and 5 meter right along the lines. Distribution research of Aquilaria spp. trees include taking its DBH for the trees that have DBH above 5 cm and taking its height for the trees that have DBH lower than 5 cm. There are 36 individuals in Line 3, Line 4, Line 5, Line 6, Line 14, Line 15, Line 16 with 3, 17, 1,3, 7,2, and 3 individuals respectively. In Line 13, no Aquilaria spp. found. From eight studied Line, Line 4 shows the highest number of individuals with 17 trees. This is because Line 4 was at foothill and it is suitable for Aquilaria spp. Most of adult Aquilaria spp that found, have DBH between 10-20cm and for the small trees, most of them have height among 20-30 cm.